ANALISIS POTENSI SEBARAN KONTAMINAN LINDI TPA TAMBAKRIGADUNG TERHADAP AIR TANAH MENGGUNAKAN MODFLOW DAN MT3DMS - Ni'mah, Mutiara Ulin; Suprayogi, Dedy; Hakim, Abdul; Auvaria, Shinfi Wazna; Falasifah, Nihlatul (Jurnal Riset Rekayasa Sipil, 2026)
Population growth, economic development, and improved public welfare in Indonesia have led to a significant increase in domestic waste generation. In Lamongan Regency, this condition has directly contributed to the growing amount of waste disposed of at the Tambakrigadung Landfill. The accumulation of large volumes of waste produces leachate, a dark-colored liquid formed through rainwater infiltration and the decomposition of organic matter. This leachate contains various hazardous pollutants, including heavy metals such as mercury (Hg) and cadmium (Cd), which can contaminate soil and groundwater. This study aims to analyze the potential distribution of leachate contaminants using GMS-based MODFLOW and MT3DMS modeling, as the first application at the Tambakrigadung Landfill. Model parameters were derived from primary and secondary data, assuming a single saturated aquifer and steady-state flow conditions. Simulations were carried out over 25 years to map groundwater flow directions and contaminant distribution patterns. The MODFLOW simulation results indicate a dominant groundwater flow direction from south to north, while MT3DMS results show that after 25 years, Hg contaminants spread approximately 112 meters with a final concentration below 0.005 mg/L, and Cd spread about 107 meters with a concentration below 0.021 mg/L. The very low RMSE values (Hg = 0.0006; Cd = 0.0002) indicate a high level of model accuracy in representing actual field conditions.